Comparison of three anti-coccidioides antibody enzyme immunoassay kits for the diagnosis of coccidioidomycosis. (11th April 2020) - Malo, Joshua; Holbrook, Eric; Zangeneh, Tirdad; Strawter, Chris; Oren, Eyal; Robey, Ian; Erickson, Heidi; Carranza-Chahal, Racquel; Durkin, Michelle; Thompson, Cindy; Hoover, Susan E; Ampel, Neil M; et al.
Abstract: Coccidioidomycosis is a common cause of community-acquired pneumonia in endemic areas of the southwestern United States. Clinical presentations range from self-limited disease to severe, disseminated disease. As such, early and accurate diagnosis is essential to ensure appropriate treatment and monitoring. Currently available diagnostic testing has variable accuracy, particularly in certain patient populations, and new tests may offer improved accuracy for the diagnosis of coccidioidomycosis. Serum samples from patients with coccidioidomycosis and controls were tested for immunoglobulin G (IgG) and immunoglobulin M (IgM) antibodies using the MVista Coccidioides antibody detection EIA and two commonly used commercial enzyme immunoassay (EIA) kits: the IMMY Omega EIA and the Meridian Premier EIA. The sensitivity of the IgG antibody detection was 87.4% using the MVista test compared to 46.6% for IMMY and 70.9% for Meridian. The sensitivity for IgM antibody detection was 61.2% for the MVista test, 22.3% for IMMY and 29.1% for Meridian. For IgG antibody detection, specificity was 90% for the MVista EIA, 94.6% for IMMY, 96.4% for Meridian. For IgM antibody detection, specificity was 95.3% for the MVista test 98.2% for IMMY and 99.1% for Meridian. The MVista Coccidioides antibody EIA offers improved sensitivity, including among high-risk patient populations, for the detection of IgG and IgM antibodies in comparison to other currently available EIAs.